Peran Pemuda dalam Mendukung E-Government di Era Pemerintahan Berbasis Digital 5.0 - Umiyati Haris; Syahrabudin Husein Enala; Syahruddin; Nurjalal (PAPSEL Research and Consulting, 2024)
This research examines the role of youth in supporting e-government in the era of digital-based government 5.0, highlighting how the younger generation can be the main agent in the digital transformation of government. In this context, youth not only act as users of technology, but also as developers of innovations that support the efficiency, transparency, and responsiveness of public services. Secondary data collected through document searches of literature, journal articles, government reports, and other official documents form the basis of this research analysis. The descriptive-analytical qualitative method is used to describe and criticise various aspects of the role of youth in e-government. Case studies such as